ӘДЕБИЙ БАЙЛАНЫСЛАР, АЎДАРМАЛАР, ИЗЕРТЛЕЎЛЕР-ҚАРАҚАЛПАҚ ЭПОСЛАРЫН СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЎДИҢ ӘҲМИЙЕТЛИ ҚУРАЛЫ СЫПАТЫНДА - Алламбергенова, Г.К. (FAN va JAMIYAT, 2021)
The article is devoted to the issues of studing the Karakalpak eposes by foreign scholars in the XX and at the beginming of the XXI centuries. There have been analyzed their research works, devoted to the study and propaganda of Karakalpak eposes. The article evaluates the German scholar Karl Roychl’s works, done at the end of the ХХ and at the beginning of the ХХI centuries, especially the study and publication of the Karakalpak folk epos «Edige» as a valuable scientific source.